Facilidades turísticas del humedal abras de mantequilla para el desarrollo del turismo inclusivo del sitio - Solis Santana, Jacksely Melissa (2021)
This case study was carried out to identify tourists facilities in the Abras de Mantequilla wetland. The study has theoretical bases related to social inclusion, accessibility, people with disabilities. The importance of inclusive tourism and its advantages, as well as information on wetlands and its characteristics was analyzed too. The methodology has a quantitative and qualitative approach. The research is descriptive and applied several techniques to obtain data, such as direct observation surveys, an interview and an accessibility form provided by the Ministry of Tourism of Ecuador. Which is an annex of the methodology for ranking attractions and generation of tourist spaces in Ecuador 2017. The main results of this case study allow us to identify the accessibility tourism facilities in the Abras de Mantequilla Wetlands. In addition, it also emerged the weaknesses of the site for the development of inclusive tourism.